مبادئ العقائدية الأساسية في بناء الحضارة الإسلامية عند ماجد عرسان الكيلاني (دراسة وصفية تحليلية من منظور التصور الإسلام) - Khalim, Muhammad Nur; Izzah, Nailul; Rahman, Ryan Arief (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Islam with its civilization has succeeded in showing its golden age for centuries, but over time the civilization began to collapse due to several things, both internal and external, in an effort to strengthen the role of religion in civilization, Majid Irsan Al-Kilani is a Muslim scholar who is able to examine the causes of the decline of Muslims, especially during the crusades carefully. This research is literature research with an Islamic Worldview approach, and aims to understand the fundamental principles of Aqidah by Majid Irsan Al-Kilani and then analyzed with several Muslim scholars. Therefore, this research uses descriptive-analytical method. This research concludes that; First, that the basic principles of Aqidah in improving civilization according to Majid Irsan Al Kilani start from worshiping Allah with Obedience and Wala, Unity of the Ummah by not being divided by the differences of some groups, enforcing religious discipline in the right way, believing that Allah is the only Creator and Humans as servants who are obliged to worship Him. To be able to restore civilization in the view of the Islamic worldview according to Al-Kilani is by remembering the sunatullah in knowledge and Ulama, justice, righteous deed